2015
DOI: 10.1039/c5ay01883h
|View full text |Cite
|
Sign up to set email alerts
|

A fluorophore-conjugated ascorbic acid functions for the visualization of sodium vitamin C transporters in living cells

Abstract: Human beings do not produce ascorbic acid (AA) and acquire AA through the sodium vitamin C transporters (SVCTs). Changes in the expression or function of SVCT proteins may be associated with human diseases. In this regard, imaging of SVCTs in living cells is important. However, the options for live-cell labelling of SVCTs were very limited. In this work, we synthesized a new small-molecule fluorescent probe RB-A-Vc, and demonstrated its application in selectively visualizing SVCTs in living cells. This probe f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…We reproduced these results in other cell types, e.g., Raw 264.7 and C2C12 myoblasts (103, unpublished data), other investigators detected SVCT2 in HEK-293T cells and reported a similar prevalent mitochondrial expression of SVCT2 (79). Another study (125) employed the same cell line to demonstrate that the high mitochondrial expression of the transporter detected by immunolocalization studies can be confirmed with the use of a novel fluorescent probe detecting SVCT2. These Authors also used HepG2 cells, which express both SVCT1 and SVCT2.…”
Section: Mitochondrial Transport Of Aa Through Svct2supporting
confidence: 84%
“…We reproduced these results in other cell types, e.g., Raw 264.7 and C2C12 myoblasts (103, unpublished data), other investigators detected SVCT2 in HEK-293T cells and reported a similar prevalent mitochondrial expression of SVCT2 (79). Another study (125) employed the same cell line to demonstrate that the high mitochondrial expression of the transporter detected by immunolocalization studies can be confirmed with the use of a novel fluorescent probe detecting SVCT2. These Authors also used HepG2 cells, which express both SVCT1 and SVCT2.…”
Section: Mitochondrial Transport Of Aa Through Svct2supporting
confidence: 84%